Hybrid Three Dimensionally Printed Paper-Based Microfluidic Platform for Investigating a Cell’s Apoptosis and Intracellular Cross-Talk - Liu, Ping; Li, Bowei; Fu, Longwen; Huang, Yan; Man, Mingsan; Qi, Ji; Sun, Xiyan; Kang, Qi; Shen, Dazhong; Chen, Lingxin (ACS sensors, 2020)
In this paper, we first proposed a novel hybrid three-dimensional (3D) printed and paper-based microfluidic platform and applied it for investigating the cell’s apoptosis and intracellular cross-talk. The fabrication of a 3D-printed microfluidic chip is much easier than polydimethylsiloxane (PDMS) chip and can be applied in many common labs without soft lithogrophy fabrication equipment. Moreover, 3D printing can be perfectly combined with paper-based chips that can provide 3D scaffold for cell culture and analysis. In addition, these paper chips are disposable after use, greatly reducing the experimental cost. We integrated “Christmas Tree” structure with the top layer of the 3D-printed microfluidic chip to generate a continuous concentration gradient, and the bottom layer contained paper-based chips as cell culture area. The two-layer structure allows the concentration gradient forming layer to be separated from the cell culture layer, which can simplify the planting of cells in the microfluidic chip and make sure the cells stay in the culture chambers and don’t clog the microfluidic channels. Applying this hybrid platform, we examined the effect of H2S on cancer cells. Continuous exposure to a low concentration of H2S inhibited cancer cell SMMC-7721 proliferation by inducing cell apoptosis. We also found that two gaseous molecules H2S and NO have cross-talk in cancer cells; they formed bioactive intermediate polysulfides in cancer cells. It is expected that this novel hybrid 3D-printed and paper-based microfluidic platform will have widespread application prospects in cell investigation.